Lipid profile and cardiovascular risk factors in pediatric liver transplant recipients. (11th January 2016) - Roblin, Emilie; Dumortier, Jérôme; Di Filippo, Mathilde; Collardeau‐Frachon, Sophie; Sassolas, Agnès; Peretti, Noël; Serusclat, André; Rivet, Christine; Boillot, Olivier; Lachaux, Alain
Abstract: Cardiovascular diseases induce long‐term morbidity and mortality of adult LT recipients. The aim of this retrospective study was to assess CVRF, lipid abnormalities, and atherosclerosis (appraised by c‐IMT), more than 10 yr after pediatric LT. Thirty‐one children who underwent LT between December 1990 and December 2000 were included. Median age at LT was 14 months (range 4–64), and median follow‐up after LT was 11.9 yr (range 9.0–17.3). In our cohort, obesity (9.7%) and treated hypertension (9.7%) were rare. None of the patients was smoker or diabetic. High TC and TG were both observed in 6.5% of the patients. The mean c‐IMT for male patients was 1.22 ± 1.55 and 1.58 ± 1.23 mm in female patients. Seven patients (22%) had a mean c‐IMT above +2 s.d. Values below the 5th percentile were noted for LDL‐cholesterol (58.1%), HDL‐cholesterol (25.8%), apolipoprotein B (40%), and apolipoprotein A1 (20%). LDL‐cholesterol and apolipoprotein B levels were significantly lower in patients treated by tacrolimus in comparison with CsA (p < 0.05). In conclusion, our results suggest that pediatric LT patients do not present significant CVRF; moreover, instead of hyperlipidemia, hypocholesterolemia (LDL‐C) is frequent and immunosuppressive therapy is probably the cause.